Production of cyclodextrin glucanotransferase by Bacillus circulans P28 using sago starch as substrate - Mansor, Azlina (2013)
The present study was undertaken to address the needs to search for novel cyclodextrin glucanotransferase (CGTase) with improved properties due to the vast diversity of cyclodextrin (CDs) applications. Lack of information pertaining to the limitation in CGTase production using sago starch, an abundant raw material available in Malaysia as substrate, has also led to this research direction. In this study, fermentation of CGTase by a locally isolated bacterium, Bacillus circulans P28, was first performed in shake flasks to optimize medium formulation and culture conditions. The fermentation process was then transferred to 2 L stirred tank bioreactor, where the requirement for aeration and agitation were studied in batch fermentation mode. Subsequently, fedbatch cultures were conducted to overcome the problem related to the effect of catabolite repression for enhancement of CGTase production. CGTase from B. circulans P28 was purified to homogeneity up to 20 fold by 40-60% ammonium sulphate precipitation and anion exchange DEAE-Cellulose with 23% recovery. The enzyme was a monomer with an estimated molecular weight of 33 kDa on the SDS-PAGE using 12% acrylamide gel electrophoresis. The enzyme was stable and active at a broad pH range (6 to 10) and was optimally active at 65°C, indicating that this enzyme may have potential for industrial application in CD production. Thermal stability was improved in the present of 2 mM CaCl2 and was stable up to 60°C for 1 h. Sago starch was the most preferred substrate for CD production by CGTase from B. circulans P28 as compared to other starches tested in this study (potato, soluble and tapioca starch). In the enzymatic reaction, mainly β-CD (78%) and γ-CD (22%) were produced, suggesting a simpler and easier CDs separation processes required in the downstream processing. The optimal conditions for CGTase fermentation by B. circulans P28 in shake flask were at 30°C and in the presence of 1% (w/v) Na2CO3 (which associated with an initial culture pH of 10.2). Optimization of the culture medium using full factorial design (FFD) approach has revealed that sago starch, yeast extract and interaction of sago starch and yeast extract significantly affected CGTase production by B. circulans P28. In fermentation using the optimized medium composition (3 g/L sago starch and 17.83 g/L yeast extract) which corresponded to C/N ratio of 0.8, the maximum CGTase activity obtained was 6.96 U/mL, which was about 45% higher than that obtained in non-optimized medium (4.6 U/mL). Production of CGTase by B. circulans P28 in 2 L stirred tank bioreactor increased propotionally with the increase in agitation speed, ranging from 400 to 900 rpm though growth was slightly inhibited at agitation speed of above 600 rpm. The shear forces created by the impeller at high agitation speed had caused cell distruption and affected the cell viability, thus, resulted in an increase in CGTase activity. The highest CGTase activity (9.6 U/ml) in batch fermentation using stirred tank bioreactor was obtained at; agitation speed of 600 rpm; air-flow rate of 0.5 vvm; initial culture pH of 10.8 without pH control during the fermentation and temperature of 30°C. This gave an improvement of 44% as compared to that obtained in optimum fermentation using shake flask. Further improvement in CGTase production by B. circulans P28 was achieved through the implementation of fed-batch fermentation. The highest overall enzyme yield (7400 U/g) and productivity (1500 U/L/h) was obtained in fed-batch fermentation fed with low concentration of starch (3 g/L) in the feed at a constant feeding rate of 0.36 g/L/h. This gave an improvement in term of maximum CGTase activity and productivity, by 104% and 49%, respectively, as compared to conventional batch fermentation. This study indicated that fed-batch fermentation is a good alternative for CGTase production by overcoming the catabolic repression effect. Many different approaches used in this study to overcome the limitations of CGTase production may find vast applications in obtaining high enzyme productivities using other CGTase-producing microorganisms and perhaps also for other starch-converting enzymes.